Waste Pickers and Their Practices of Insurgency and Environmental Stewardship - Gutberlet, Jutta (2021)
Informed by different grassroots learning and educational practices engaged in waste management, and drawing from the concepts of insurgent citizenship and environmental stewardship, we examine the role of waste picker organizations and movements in creating new pathways towards more sustainable environmental waste governance. Two case studies (Argentina and Brazil) demonstrate how waste pickers inform and educate the general public and raise the awareness of socio-environmental questions related to waste management. Different educational practices are used as strategies to confront citizens with their waste: to see waste as a consumption problem, resource, and income source. Our paper draws on grassroots learning (social movement learning and insurgent learning) and education (stewardship) aimed at the transformation of waste practices. We argue that waste pickers play an important role in knowledge production promoting recycling, in landfilling less and recovering more resources. We conclude that waste pickers act as insurgent citizens and also are environmental stewards.